2018
DOI: 10.7150/jca.25956
|View full text |Cite
|
Sign up to set email alerts
|

Identification of microRNA-124 in regulation of Hepatocellular carcinoma through BIRC3 and the NF-κB pathway

Abstract: MicroRNAs (miRNAs) being proved to be involved in the carcinogenesis of numerous tumors. MicroRNA-124 (miR-124), identified as a tumor suppressor, has been demonstrated to exert pivotal roles in multiple processes of tumorigenesis. The present study demonstrated that miR-124 was low-expressed in human hepatocellular carcinoma (HCC) tissues and cell lines. In addition, overexpression of miR-124 through infected with miR-124 lentivirus inhibited the proliferation and migration of HCC in vitro and tumorigenesis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 34 publications
4
27
0
Order By: Relevance
“…Another HCC‐related study demonstrated that miR‐124 could further inhibit the proliferation of HCC cells (SMMC‐7721) by regulating Baculoviral IAP Repeat Containing 3 (BIRC3) and controlling the NF‐kB pathway and migration. The author also pointed out that miR‐124 was a therapeutic target for the prognosis of HCC . Other scholars have also pointed out that in two liver cancer cell lines (SMMC‐7721 and BEL‐7404), miR‐124 could regulate Sp1 expression and inhibit cell migration and invasion .…”
Section: Mir‐124 and Hepatocellular Carcinomamentioning
confidence: 98%
See 1 more Smart Citation
“…Another HCC‐related study demonstrated that miR‐124 could further inhibit the proliferation of HCC cells (SMMC‐7721) by regulating Baculoviral IAP Repeat Containing 3 (BIRC3) and controlling the NF‐kB pathway and migration. The author also pointed out that miR‐124 was a therapeutic target for the prognosis of HCC . Other scholars have also pointed out that in two liver cancer cell lines (SMMC‐7721 and BEL‐7404), miR‐124 could regulate Sp1 expression and inhibit cell migration and invasion .…”
Section: Mir‐124 and Hepatocellular Carcinomamentioning
confidence: 98%
“…The author also pointed out that miR-124 was a therapeutic target for the prognosis of HCC. 44 Other scholars have also pointed out that in two liver cancer cell lines (SMMC-7721 and BEL-7404), miR-124 could regulate Sp1 expression and inhibit cell migration and invasion. 45 Lu et al further confirmed that miR-124 suppressed HepG-2 cell proliferation by reducing STAT3 protein expression levels, and overexpressed miR-124 could significantly promote HCC apoptosis.…”
Section: Hepatocellular Carcinomamentioning
confidence: 99%
“…miR-124 is highly expressed in the brain and was previously demonstrated to be a ‘brain-enriched’ miRNA (10,11). In recent years, researchers have demonstrated that the expression of miR-124 is dysregulated in almost all tumors, such as colorectal cancer (27), gastric cancer (28), lung cancer (16) and hepatocellular carcinoma (29). In the progression of cancer, miR-124 not only acts as a suppressor of tumor growth but also decreases cell invasion and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Further, several studies indicate that targets of miR-124-3p promote cellular proliferation and migration in several cancers, including hepatocellular carcinoma [74,75], oral squamous cell carcinomas [76], and gastric cancer [77]. Moreover, in vitro studies demonstrated that transfection of premiR-124-3p in hepatocellular carcinoma cells induces apoptosis and limits proliferation [78,79]. Whether or not the apoptosis is triggered by pushing the non-neuronal cells toward a neuronal identity requires further clarification.…”
Section: Downregulation Of Mir-124-3p Promotes Neurodegenerationmentioning
confidence: 99%